2021
DOI: 10.11606/issn.1678-4456.bjvras.2021.174336
|View full text |Cite
|
Sign up to set email alerts
|

Use of sulfonamides for the treatment of bovine neonatal diarrhea: clinical and performance parameters

Abstract: This study was developed to evaluate the clinical, hematological, and performance parameters of calves affected by diarrhea caused by the bacterial enteric pathogen Escherichia coli, treated with three different protocols containing sulfonamides. Fourteen Holstein calves were monitored from birth to 60 days of age, and divided into 3 groups. Group 1 (n=5) animals were treated with 80 g of Kaopek®, Ibasa, Brazil, administered orally (BM), dissolved in 160 ml of water every 24 h; Group 2 (n=4) received IM sulfad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several enteric pathogens are responsible for causing neonatal diarrhea [ 27 ]. In this study, 36 E. coli (100%) and 12 Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several enteric pathogens are responsible for causing neonatal diarrhea [ 27 ]. In this study, 36 E. coli (100%) and 12 Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…Variation in results of TVC, TEC, and TSC indicates that sulfonamide is not always effective for diarrheic calves. In this regard, Klaus et al [27] reported that sulfonamides used for the treatment of neonatal calves with diarrhea were effective in their clinical improvement, but systemic therapy with sulfonamide plus antibiotics provided better performance, with better weight gain and body development.…”
Section: Enumeration Of Tvc Tec and Tsc From Diarrheic Calvesmentioning
confidence: 99%
“…Antibiotic therapy is recommended in such cases because these pathogens spread rapidly in the small intestine of calves, causing clinical complications and widespread environmental contamination (Constable 2009; Klaus et al . 2021). Metritis is another disease of global importance, which affects approximately 20% of lactating cows and generates at a cost of $600 million for the American dairy industry alone (Overton and Fetrow 2017; Ma et al .…”
Section: Antibiotics Used In Brazilian Dairy Productionmentioning
confidence: 99%